Geochemical evaluation pollution for some heavy metals in basra soil - Al-Bedhany, Abbas (University of Thi-Qar Journal of Science, 2019)
iron. Basra contaminated soil with heavy elements increase is attributable to human and industrial activities such as increased transportation vehicles and burning gasoline and from other facilities such as hospitals, power plants and oil companies, as well as the use of phosphate fertilizers in agricultural areas, as well as some industrial parks to increase concentrations of some heavy metals in the soil. Keyword: heavy metal, Soil, Total organic carbn(TOC %), Grain size analysis, Geochemical index (Igeo), iron. Basra contaminated soil with heavy elements increase is attributable to human and industrial activities such as increased transportation vehicles and burning gasoline and from other facilities such as hospitals, power plants and oil companies, as well as the use of phosphate fertilizers in agricultural areas, as well as some industrial parks to increase concentrations of some heavy metals in the soil.